2010
DOI: 10.1080/13554790903070265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of regional cerebral blood flow in a patient with musical hallucinations

Abstract: A 52-year-old woman with musical hallucinations was examined using brain single photon emission computed tomography (SPECT) with 99mTc-ECD. Changes in regional cerebral blood flow (rCBF) after carbamazepine treatment were assessed using a three-dimensional stereotaxic ROI template. Following treatment, rCBF was decreased in the subcortical structures and increased in the global cortical regions. From our findings, we propose that rCBF values in subcortical structures represent abnormalities similar to those re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…More recently, Cavaliere et al [ 9 ] studied the fronto-temporal circuits involved in MH to determine if there is a morpho-functional circuit consistently involved in the development or experience of MH. That study, like previous research [ 23 ], showed functional connectivity in multiple cortical regions, or that there is inconsistent involvement of subcortical sections.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…More recently, Cavaliere et al [ 9 ] studied the fronto-temporal circuits involved in MH to determine if there is a morpho-functional circuit consistently involved in the development or experience of MH. That study, like previous research [ 23 ], showed functional connectivity in multiple cortical regions, or that there is inconsistent involvement of subcortical sections.…”
Section: Introductionsupporting
confidence: 87%
“…The current case is comparable to a case reported by Razdan et al [ 18 ] in which a patient had MH and hearing loss without any associated neuropsychiatric disorder. Such findings indicate that hearing loss is a common occurrence in individuals with MH [ 19 , 23 , 27 ]. To assess our patient’s experience of MH, a combination of clinical and cognitive assessment was used, in addition to functional and structural MRI, to investigate the neural basis of MH.…”
Section: Discussionmentioning
confidence: 99%
“…Some 11 articles were identified. [6][7][8][9][10][11][12][13][14][15][16] We excluded two articles that were unrelated to the topic. 12,13 In addition to the PubMed search, nine other relevant clinical case reports of functional neuroimaging studies on MHs were identified based on bibliographies and our knowledge of the subject.…”
Section: Methodsmentioning
confidence: 99%
“…As Zatorre and Halpern (2005) speculate, “Feedback signals from auditory cortex could be important in distinguishing between imagery and a real sound coming from the environment” (p. 10); we can now add that it is most likely that an activation of the primary auditory cortex determines whether a sound source is perceived as real or as imagery. Shoyama et al (2010) present one case where the sound source is located in the head and simultaneously considered real (p. 3). By means of electroencephalogram (EEG), subcortical and cortical regions were found to be active.…”
Section: Possible Neural Substrates and The Role Of The Primary Audit...mentioning
confidence: 99%